Foreign Policy of Nepal: Diplomatic Relations With China - Kanwar, Kalidas (GS WOW: Wisdom of Worthy Research Journal, 2025)
The study article “Foreign Policy of Nepal: Diplomatic Relationship with China” offers a critical examination in the domain of International Relations, concentrating on Nepal’s foreign policy and its diplomatic relations with China. It looks at how bilateral relations work and the different types of diplomatic understanding that affect how countries act in politics around the world. The research seeks to cultivate an International Relations viewpoint grounded in the tenets of foreign policy and diplomacy, providing elucidation on regional and global political frameworks. China's role is highlighted as a significant influence on Nepal's foreign policy direction and international relations. The study employs a descriptive research methodology, utilizing secondary data sourced from academic publications, journal articles, official reports, and policy papers pertaining to foreign policy, diplomacy, and international relations. It examines significant elements, including political, economic, military, cultural, and religious relations, as well as the dynamics of power exchange, conflict, and collaboration between Nepal and China. The study also shows how the roles of state actors are changing and how Nepal's foreign policy is becoming more flexible in dealing with political problems at home and abroad.electronics.